Deteksi Pencemaran Bakteri Escherichia coli pada Produk Perikanan untuk Keamanan Bahan Pangan bagi Masyarakat - Hardestyariki, dwi; Yurikko, Aldila Mouli; Novita, Rennie Puspa; Amriani, Annisa; Agustiarini, Vitri (MESINA (Medical Scientific Journal), 2025)
Fish  is a fishery product that has high nutrition and is very popular with the community and can be consumed with various processed foods. However, the existence of unmaintained sanitation in ponds or fish breeding grounds causes frequent contamination by unwanted pathogenic microbes such as E. coli. This study aims to identify E. coli bacterial contamination in fresh fish samples and analyze the amount of contamination that exceeds the quality standards set by SNI. The method used in this microbiological test refers to SNI 2332.1:2015 including presumptive test, confirmed test, and completed test. This research activity was carried out for 1 month at the UPTD for the Submission and Application of Fishery Product Quality (PPMHP). The results of the study showed that the fish samples examined were detected for E.coli bacterial contamination with the number of E.coli bacteria in fish samples of <3 MPN/g which means that the value does not exceed the quality standards set by SNI 2332.1:2015. Meanwhile, the total number of Coliforms showed a value of 93 MPN/g which exceeded the set quality standard. This indicates the need to increase supervision and quality control on fishery products to ensure food safety for people who consume fish.